Studi Literatur: Implementasi Model Pembelajaran Discovery Learning Terhadap Peningkatan Hasil Belajar Peserta Didik Materi Kimia SMA - Pristiana, Chofifah Puji; Safitri, Hasna Hanifah; Rahmawan, Setia (Universitas Papua, Manokwari, Indonesia, 2024)
The aim of this research is to characterize the extent to which the discovery learning model can improve student learning outcomes in high school chemistry material and the impact of this model on classroom learning. This research employs a descriptive-qualitative literature study methodology, based on the publication of scientific journal articles. The findings of this research indicate that the discovery learning model, when applied in each cycle, will improve learning outcomes, thus indicating that this model may be a substitute for conventional chemistry teaching methods. However, this model also requires reflection, adjustment, and continuous improvement in the learning process